2018
DOI: 10.1007/s00170-018-1950-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surface extraction techniques performance in computed tomography for 3D complex micro-geometry dimensional measurements

Abstract: The number of industrial applications of Computed Tomography (CT) for dimensional metrology in 10 0-10 3 mm range has been continuously increasing, especially in the last years. Due to its specific characteristics Computed Tomography has the potential to be employed as a viable solution for measuring 3D complex micro-geometries as well (i.e. in the sub-mm dimensional range). However, there are different factors that may influence the CT process performance, being one of them the surface extraction technique us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The number of industrial applications of computed tomography (CT) for dimensional metrology has increased significantly, and CT is employed for measuring 3D complex microgeometries [48]. Buratti et al [49] indicated that CT played a key role in 3D coordinate metrology as an alternative to conventional coordinate measuring machines and enhanced and validated an analytical method for optimising imaging parameters.…”
Section: Non-traditional Measurement Equipment and Methodsmentioning
confidence: 99%
“…The number of industrial applications of computed tomography (CT) for dimensional metrology has increased significantly, and CT is employed for measuring 3D complex microgeometries [48]. Buratti et al [49] indicated that CT played a key role in 3D coordinate metrology as an alternative to conventional coordinate measuring machines and enhanced and validated an analytical method for optimising imaging parameters.…”
Section: Non-traditional Measurement Equipment and Methodsmentioning
confidence: 99%
“…Expanded measurement uncertainties with level of confidence of 95% ( U 95 ) were calculated according to ISO 14253-2 [ 16 , 20 ] for each one of the measurements carried out over the air wedge gap of the Al/Ti multi-material standard. This standard takes into account the uncertainty contributions related to the CT system length measurement errors with respect to the reference measurements performed with the micro-CMS Zeiss F35, the repeatability of the measurement procedure assessed from five repetitions of the full measurement process (scan, reconstruction, surface determination and measurement) and other uncertainty contributors related to the samples material and temperature stability during the CT measuring process.…”
Section: Methodsmentioning
confidence: 99%
“…One based on the Canny algorithm [ 13 ] and another based on the Deriche algorithm [ 14 , 15 ]. These algorithms have been tested using parts with different geometries: round, flat and freeform [ 16 ]. They have also been tested using a polymer multi-material standard [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate segmentation has long been a challenge across various scientific domains, from medical CT imaging to material sciences and engineering (Withers et al, 2021). Global segmentation methods, such as manual histogram or watershed thresholding, have long been go-to solutions for the segmentation of X-ray CT tomographic images.…”
Section: Comparison With Other Segmentation Approachesmentioning
confidence: 99%